2011
DOI: 10.1016/s0377-1237(11)60012-9
|View full text |Cite
|
Sign up to set email alerts
|

Role of prophylactic surfactant in preterm infants

Abstract: INTRODUCTIONRespiratory distress syndrome (RDS) in preterm neonates is caused by a deficiency or dysfunction of pulmonary surfactant. Surfactant lines the alveolar surface and prevents atelectasis at end expiration. Pulmonary surfactant is predominantly dipalmitoylphosphatidylcholine with lesser amounts of other phospholipids including phosphatidylglycerol, phosphatidylethanolamine, and phosphatidylinositol. Pulmonary surfactant also contains neutral lipids and distinct surfactant proteins. The physiologic fun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…However, the cost of medication has remained constant over time, including that of pulmonary surfactants and respiratory syncytial virus monoclonal antibodies (Synagis®, palivizumab), which are covered by national insurance since 2010. 11,13,14 19 Beam et al, also suggested that total cost has been rising through recent years as well.…”
Section: Discussionmentioning
confidence: 99%
“…However, the cost of medication has remained constant over time, including that of pulmonary surfactants and respiratory syncytial virus monoclonal antibodies (Synagis®, palivizumab), which are covered by national insurance since 2010. 11,13,14 19 Beam et al, also suggested that total cost has been rising through recent years as well.…”
Section: Discussionmentioning
confidence: 99%